Simultaneous dimming and brightening under all and clear sky at CamagUey, Cuba (1981-2010) - Carlos Antuna-Marrero, Juan; Garcia, Frank; Estevan, Rene; Barja Gonzalez, Boris; Sanchez-Lorenzo, Arturo (My University, 2019)
The annual trends of the all sky (Eg down arrow A(sky)) and clear sky global horizontal irradiances (Eg down arrow C-sky) for the climatologically standard period 1981-2010 at Camagiiey, Cuba, are negative and positive respectively, showing the simultaneous occurrence of dimming and brightening phenomena. Positive cloud cover (CC) annual trend, is among the plausible causes of the Eg down arrow A(sky) dimming. The Eg down arrow C-sky annual mean increasing trend could be explained in part by the decreasing broadband aerosol optical depth trend. For the 1981-2016 a period non-standard climatologically the absolute magnitudes of the trends decrease for both Eg down arrow A(sky) and Eg down arrow C-sky annual means, with no change in their signs but becoming non-significant statistically. That feature resembles an attenuation process for both dimming and brightening. The series of Eg down arrow and CC observations were subject of test for determining in homogeneities identifying change points. For each one of the Eg down arrow A(sky) and Eg down arrow C-sky and CC series show no change point statistically significant. The consistency and stability of the Eg down arrow A(sky) annual means series were tested using measured and calculated Eg down arrow annual means for conditions where the solar disk is empty of clouds. The magnitudes and signs of trends for the measured and calculated Eg down arrow, annual means are very similar and both are statistically significant at the same level, confirming the series of Eg down arrow A(sky) annual means are consistent and stable.
Keywords: Trend analysis